Apoptotic vesicles rescue impaired mesenchymal stem cells and their therapeutic capacity for osteoporosis by restoring miR-145a-5p deficiency - Rong Zhang; Xiaodan Mu; Dawei Liu; Chider Chen; Bowen Meng; Yan Qu; Jin Liu; Runci Wang; Chuanjie Li; Xueli Mao; Qintao Wang; Qingbin Zhang (Journal of Nanobiotechnology, 2024)
Abstract Apoptotic vesicles (apoVs) play a vital role in various physiological and pathological conditions. However, we have yet to fully understand their precise biological effects in rescuing impaired mesenchymal stem cells (MSCs). Here, we proved that systemic infusion of MSCs derived from wild-type (WT) mice rather than from ovariectomized (OVX) mice effectively improved the osteopenia phenotype and rescued the impaired recipient MSCs in osteoporotic mice. Meanwhile, apoVs derived from WT MSCs (WT apoVs) instead of OVX apoVs efficiently restored the impaired biological function of OVX MSCs and their ability to improve osteoporosis. Mechanistically, the reduced miR-145a-5p expression hindered the osteogenic differentiation and immunomodulatory capacity of OVX MSCs by affecting the TGF-β/Smad 2/3-Wnt/β-catenin signaling axis, resulting in the development of osteoporosis. WT apoVs directly transferred miR-145a-5p to OVX MSCs, which were then reused to restore their impaired biological functions. The differential expression of miR-145a-5p is responsible for the distinct efficacy between the two types of apoVs. Overall, our findings unveil the remarkable potential of apoVs, as a novel nongenetic engineering approach, in rescuing the biological function and therapeutic capability of MSCs derived from patients. This discovery offers a new avenue for exploring apoVs-based stem cell engineering and expands the application scope of stem cell therapy, contributing to the maintenance of bone homeostasis through a previously unrecognized mechanism.